V.ii.5. School drawing account of Charles Napier Kennedy - Cheltenham College; Kennedy, Charles Napier, 1852-1898 (1866)
A Cheltenham College drawing and book account of C.N. Kennedy, for the half-year ending midsummer 1866, listing items purchased and expenses incurred.